Pemberian Fenitoin Oral dan Timbulnya Hiperplasia Ginggiva pada Pasien Epilepsi - Tranggono Yudo Utomo; Amin Husni; Farichah Hanum (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTPhenytoin oral treatment and the development of ginggival hyperplasia in epileptic patientsBackground: Phenytoin is commonly used as a first line drug therapy for epilepsy because of its potency and low cost. Dosage and duration of oral phenytoin administration have been considered as important factors in the development of ginggival hyperplasia.Objective: To investigate whether dosage and duration of oral phenytoin usage were risk factors of ginggival hyperplasia in epileptic patients.Method: Twenty epileptic patiens with phenytoin monotherapy who developed ginggival hyperplasia, and 20 epileptic patients with phenytoin monotherapy without ginggival hyperplasia as a control group were studied. The history of illness, physical examination, fasting and post prandial blood glucose level, funduscopy, oral hygiene, index of hyperplasia scoring from Saymor were taken. Blood sample 3-5 cc were also taken to examine the level of phenytoin. Oral dose, serum dose and duration of administration were noted. Odd ratio was calculated by multiple regression statistic (95% confidence interval).Result: High dose of oral phenytoin was a significant risk factor of ginggival hyperplasia, (p<0.05), while duration of administration >6 months was not a risk factor (p=0.522). Adjusted by duration of oral phenytoin usage, high dose of oral phenytoin usage was still a significant risk factor for gingival hyperplasia, OR=29.14 (95%CI 3.8-291.9).Conclusion: High dose of phenytoin was a significant risk factor for ginggival hyperplasia.Keywords: Dosage and duration of phenytoin administration, ginggival hyperplasiaABSTRAKLatar belakang: Fenitoin sering digunakan sebagai lini pertama pengobatan epilepsi karena potensial dan ekonomis. Dosis dan lama pemberian fenitoin, dianggap sebagai faktor yang berperan dalam timbulnya hiperplasia ginggiva. Tujuan penelitian ini mengetahui apakah dosis fenitoin yang tinggi dan durasi pemberian fenitoin yang panjang merupakan faktor risiko terhadap timbulnya hiperplasia ginggiva pada penderita epilepsi.Metode: Dua puluh pasien epilepsi dengan monoterapi fenitoin yang mengalami hiperplasia ginggiva dan dua puluh pasien epilepsi dengan monoterapi fenitoin yang tidak hiperplasia ginggiva diambil sebagai studi kasus kontrol. Dilakukan anamnesa, pemeriksaan fisik, gula darah puasa dan postprandial, funduskopi, higine mulut, skoring hiperplasia Indek Saymor, pengambilan sampel darah serum fenitoin 3-5cc. Selanjutnya mendata dosis oral, dosis serum dan lama pemberian. Rasio odds (95% interval kepercayaan) dihitung dengan statistik multiple regresi.Hasil: Dosis tinggi fenitoin merupakan faktor risiko yang signifikan terhadap risiko hiperplasia ginggiva (p<0,05), sementara lama pemberian obat >6 bulan tidak terbukti sebagai faktor risiko (p=0,522). Bila dikendalikan oleh faktor durasi, maka besar dosis fenitoin oral tetap merupakan faktor risiko hiperplasia ginggiva yang signifikan OR=29,14 (95%CI, 38-291,9) sedang lama pemberian fenitoin tetap bukan merupakan faktor risiko yang signifikan.Simpulan: Dosis tinggi fenitoin merupakan faktor risiko yang signifikan terhadap hiperplasia ginggiva.